"El Gratis" (1842-1843). Approximation to the study of an innovative newspaper - Feliu García, Emilio; Fernández Poyatos, Dolores (Estudios sobre el Mensaje Periodístico, 2012)
This paper presents an analysis of El Gratis, advertisements journal published in 1842-43, some of whose traits (enforcement of the double market law, free distribution of several copies, publishing a newspaperposter ...) represent a real novelty for its time and for the history of nineteenth-century journalism in Spain.
Keywords: history of journalism; 19th Century; daily press; advertising newspaper; free journals.